2004
DOI: 10.1590/s1415-47572004000400011
|View full text |Cite
|
Sign up to set email alerts
|

Population structure, fluctuating asymmetry and genetic variability in an endemic and highly isolated Astyanax fish population (Characidae)

Abstract: Morphological and chromosomal markers were used to infer the structure and genetic variability of a population of fish of the genus Astyanax, geographically isolated at sinkhole 2 of Vila Velha State Park, Paraná, Brazil. Two morphotypes types were observed, the standard phenotype I and phenotype II which showed an anatomical alteration probably due to an inbreeding process. Fluctuating asymmetry (FA) analysis of different characters showed low levels of morphological variation among the population from sinkho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
0
14
0
2
Order By: Relevance
“…fasciatus karyotype at Furna 2, previously described by Gross et al (2004), was reanalyzed and its karyotypic structure confirmed, corresponding to cytotype A. In truth, according to previous studies of Matoso et al (2002), this cytotype also characterizes the Astyanax aff.…”
Section: Et Al 2003) As Is Also Observed In Astyanax Scabripinnismentioning
confidence: 62%
“…fasciatus karyotype at Furna 2, previously described by Gross et al (2004), was reanalyzed and its karyotypic structure confirmed, corresponding to cytotype A. In truth, according to previous studies of Matoso et al (2002), this cytotype also characterizes the Astyanax aff.…”
Section: Et Al 2003) As Is Also Observed In Astyanax Scabripinnismentioning
confidence: 62%
“…In Astyanax scabripinnis (Jenyns, 1842) inhabiting different small streams, besides extensive chromosome divergences observed between populations (Moreira-Filho and Bertollo, 1991), a significant population differentiation has also been reported through a molecular analysis between putative isolated populations, although the mechanisms (selection and/or genetic drift) responsible for such genetic differentiation remain unknown (Sofia et al, 2006). Moreover, sex ratio deviation seems to be a common occurrence among this fish group and is likely related to behavioral and ecological strategies to quickly occupy the headwaters in which they live (Gross et al, 2004), but may reduce genetic variation by reducing the effective population number (Frankham et al, 2002) and lead to population differentiation.…”
Section: Small Isolated Populationsmentioning
confidence: 91%
“…Populations structured by habitat fragmentation due to barriers such as roads, dams, waterfalls and climate (drought and rain) have their abundance, dispersal and population size reduced, thereby increasing the risk of extinction (Gross et al, 2004;Letcher et al, 2007). This fragmentation can lead to the total or partial isolation of a population, conditioning the response of the individuals.…”
Section: Small Isolated Populationsmentioning
confidence: 99%
“…Astyanax have presented an extensive diversity in the chromosome number and karyotype formula, both intra-and interspecifically, besides the occurrence of B chromosomes and natural polyploidy for some populations (Malacrida et al, 2003;Gross et al, 2004;Kantek et al, 2007;Peres et al, 2009;Santos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%